Seed germination and dormancy of Miconia chartacea (Melastomataceae) in response to light, temperature and plant hormones. - Escobar Escobar, Diego F.; Cardoso, Victor J. M. (Revista de Biología Tropical, 2015)
Miconia chartacea is a widely distributed tree along both altitudinal and latitudinal gradients in Brazil, and it can be found in seasonal xerophytic vegetation, e.g. Caatinga and Cerrado, and tropical rainforest (e.g. Mata Atlantica), from grassland with scattered trees to mature forest. We studied the germination response of M. chartacea seeds to light, temperature, plant hormones and after-ripening at low temperature. Seeds were collected from a Cerrado reserve located in Corumbataí, Sao Paulo State, which characterizes to have a cool dry season from April to September, and a warm wet season from October to March. M. chartacea seeds are dispersed in the dry season and exhibited a photoblastic behavior both at constant and alternating temperatures. The germination was decreased at irradiances below 17 μmol / m2s, whereas R: FR ratios below 0.4 reduced the germination rate, but not the germination capacity. The germination-permissive temperatures range from 15 to 35 °C, with an optimum interval from 20 to 25 °C. Germination is not improved by alternating temperature regimes as compared to isothermal treatments. The seeds have a non-deep physiological dormancy, which can be partially overcame either by dry after-ripening at 7 °C for 93 days, or by the 2-chloroethylphosphonic acid treatment. The thermal window within which the seeds germinate was narrower for seeds matured in the rainy to dry season transition period, under warmer conditions, than in the dry season. Cold requirement for dormancy break in seeds of M. chartacea can prevent the germination in the winter, allowing the seeds to germinate in the summer under more favorable conditions. The results suggest that seed response to temperature accounts for temporal distribution of germination, of M. chartacea, while light predominantly influences the spatial distribution of seedlings, precluding the germination of buried seeds and affecting the germination response to gap size.